Studies on the Alocasia Schott (Araceae) of Borneo III : Alocasia puncakborneensis, a new species belonging to the Princeps Complex - Wong, Sin Yeng; Boyce, Peter C. (Firenze University Press, 2020)
Alocasia puncakborneensis is described and illustrated as a new species of the Alocasia Princeps Complex from upper hill forest on the extremely hard Paleogene sandstones of the Penrissen range, SW Sarawak. Alocasia puncakborneensis occurs at the highest altitude of any of the locally-restricted /geologically obligated species yet described for the Princeps Complex.